A new species of Tekellina (Araneae, Araneoidea) from the Russian Far East - Marusik, Yuri; Omelko, Mikhail (Entomologica Fennica, 2017)
A new species, Tekellina yoshidai sp. n., is described based on the holotype female from the Maritime Province of Russia. It is the first record of the genus in Russia and the northernmost record in the entire range. The new species is most similar to T. sadamotoi Yoshida & Ogata, 2016 from Japan. Figures are provided for both species. The male palp of T. sadamotoi was studied with a SEM. It was found that palpal sclerites in T. sadamotoi and other Tekellina species are incorrectly homologized. Judging from the structure of the male palp and the female palpal claw, Tekellina seems to be misplaced in Theridiidae and belongs elsewhere.